2006
DOI: 10.1002/hep.21343
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic response–guided therapy for prevention of variceal rebleeding

Abstract: The clinical usefulness of assessing hemodynamic response to drug therapy in the prophylaxis of variceal rebleeding is unknown. An open-labeled, uncontrolled pilot trial was performed to evaluate the feasibility and efficacy of using the hemodynamic response to pharmacological treatment to guide therapy in this setting. Fifty patients with acute variceal bleeding underwent a hepatic venous pressure gradient (HVPG) measurement 5 days after the episode. Nadolol and nitrates were initiated, and a second HVPG was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 38 publications
0
30
0
4
Order By: Relevance
“…19,36 In patients who are HVPG responders, it would not be rational to use endoscopic therapy. As suggested recently, perhaps the most rational therapy would be to adapt the different therapies to prevent variceal rebleeding in the context of HVPG response 125,126 ; however, this would require standardization of the HVPG technique, including the best timing to perform the repeat HVPG measurement. Existing studies have performed the second HVPG measurement a median of 90 days after the first measurement (range 19-159 days), and there is evidence suggesting that the predictive value of the change in HVPG is reduced with increasing time between measurements.…”
Section: E Patients With Cirrhosis Who Have Recovered From Acute Varmentioning
confidence: 99%
“…19,36 In patients who are HVPG responders, it would not be rational to use endoscopic therapy. As suggested recently, perhaps the most rational therapy would be to adapt the different therapies to prevent variceal rebleeding in the context of HVPG response 125,126 ; however, this would require standardization of the HVPG technique, including the best timing to perform the repeat HVPG measurement. Existing studies have performed the second HVPG measurement a median of 90 days after the first measurement (range 19-159 days), and there is evidence suggesting that the predictive value of the change in HVPG is reduced with increasing time between measurements.…”
Section: E Patients With Cirrhosis Who Have Recovered From Acute Varmentioning
confidence: 99%
“…In patients who are HVPG responders, it would not be rational to use endoscopic therapy. As suggested recently, perhaps the most rational therapy would be to adapt the different therapies to prevent variceal rebleeding in the context of HVPG response (125,126); however, this would require standardization of the HVPG technique, including the best timing to perform the repeat HVPG measurement. Existing studies have performed the second HVPG measurement a median of 90 days after the first measurement (range 19-159 days), and there is evidence suggesting that the predictive value of the change in HVPG is reduced with increasing time between measurements (19).…”
Section: E Patients With Cirrhosis Who Have Recovered From Acute Varmentioning
confidence: 99%
“…Patients with a reduction in HVPG to less than 12 mmHg or a reduction in HVPG by more than 20% have the lowest rate of variceal rebleeding, about 10% [D'Amico et al 2006;Bosch and Garcia-Pagán, 2003]. It has been suggested that such patients could be treated with pharmacological treatment alone without endoscopic variceal ligation until eradication [Bureau et al 2002;Gonzalez et al 2006]. However, HVPG measurements are made only in referral centres and cannot be used for clinical practice.…”
Section: Secondary Prophylaxismentioning
confidence: 99%